Autologous CD34+ Stem Cell Therapy Increases Coronary Flow Reserve and Reduces Angina in Patients With Coronary Microvascular Dysfunction. (February 2022) - Henry, Timothy D.; Bairey Merz, C. Noel; Wei, Janet; Corban, Michel T.; Quesada, Odayme; Joung, Sandy; Kotynski, Christine L.; Wang, Jian; Lewis, Michelle; Schumacher, Ann M.; Bartel, Ronnda L.; Takagi, Hiroshi; et al.
Abstract : Background: Coronary microvascular dysfunction results in angina and adverse outcomes in patients with evidence of ischemia and nonobstructive coronary artery disease; however, no specific therapy exists. CD34+ cell therapy increases microvasculature in preclinical models and improves symptoms, exercise tolerance, and mortality in refractory angina patients with obstructive coronary artery disease. The objective of this research was to evaluate the safety, tolerability, and efficacy of intracoronary CD34+ cell therapy in patients with coronary microvascular dysfunction. Methods: We conducted a 2-center, 20-participant trial of autologous CD34+ cell therapy (protocol CLBS16-P01; NCT03508609) in patients with ischemia and nonobstructive coronary artery disease with persistent angina and coronary flow reserve ⩽2.5. Efficacy measures included coronary flow reserve, angina frequency, Canadian Cardiovascular Society angina class, Seattle Angina Questionnaire, SF-36, and modified Bruce exercise treadmill test obtained at baseline and 6 months after treatment. Autologous CD34+ cells (CLBS16) were mobilized by administration of granulocyte-colony stimulating factor 5µg/kg/day for 5 days and collected by leukapheresis. Participants received a single intracoronary left anterior descending infusion of isolated CD34+ cells in medium that enhances cell function. Results: Coronary flow reserve improved from 2.08±0.32 at baseline to 2.68±0.79 at 6 months after treatment ( P <0.005). Angina frequency decreased ( P <0.004), Canadian Cardiovascular Society class improved ( P <0.001), and quality of life improved as assessed by the Seattle Angina Questionnaire ( P ⩽0.03, all scales) and SF-36 ( P ⩽0.04, all scales). There were no cell-related serious adverse events. Conclusions: In this pilot clinical trial of microvascular angina, patients with ischemia and nonobstructive coronary artery disease receiving intracoronary infusion of CD34+ cell therapy had higher coronary flow reserve, less severe angina, and better quality of life at 6 months. The current study supports a potential therapeutic role for CD34+ cells in patients with microvascular angina. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03508609.